(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
This study demonstrates the implementation of an interdisciplinary project in the field of fashion, focusing on the development of a baby layette collection involving 5th-period fashion students in the curricular components named Experiential Learning, specifically ABEX IV - Fashion Research and Creation, and ABEX V - Fashion Project. Titled "Self Love: Mommies and the baby’s layette"," the pieces were intended for needy mothers, patients at the Regional Hospital of the West (HRO), through the Association of Volunteers of the Regional Hospital of the West (AVHRO). The theoretical aspect of this work involved concepts and foundations related to extension activities in the academic curriculum and the recognition of the social role of the fashion professional. In professional practice, the project provided students with insights into project methodology, pattern-making, and garment construction improvement practices. A total of 432 pieces were produced for the maternity kit and donated to AVHRO.